Contribuiçã ao estudo de caracterizaçã de depó formados no papel - Santos, Francisco José Dos [UNESP]; Jafelicci Júnior, Miguel [UNESP]; Morishita, Gabriela; De Oliveira, Reginaldo; Almeida, Séb (My University, 2008)
Deposits formed on the surface of. paper were analysed in order to identify the sources of the defects, as well as to solve the problems associated with performance and adjustments at the wet end of the paper forming process. Standard paper samples containing deposits were collected and analysed by comparing the microstructure and composition of the deposit with paper regions adjacent to it. Optical microscopy (OM). energy dispersive X-ray microanalysis (EDX) X-ray powder diffraction (XRD). thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) were the techniques used in this study. The results obtained from the EDX, XRD. and TG techniques allowed concluding that the calcium carbonate content in the farm of calcite is 1.6 times higher in the formed deposit them the quantity expected in the standard paper composition. The paper sample microstructure revealed by the SEM images indicates the presence of irregular spherical aggregates up to 20μm in diameter in the deposit region. containing larger amount of calcium carbonate as well as in the regions adjacent to the deposit. These spherical aggregates seem to be absorbed and integrated into the pulp fibres and present characteristics similar to those of partially cooked cationic starch. The analysed deposits are characterised by a dense and thick substance, forming a plate with highly adhesive property. This adhesive substance has a characteristic similar to glue with a large amount of organic matter due to the high weight loss shown by the TG curve. The results are consistent with the interaction ofparticles of negatively charged calcium carbonate and cationic starch, forming sterically stabilized deposits, which firmly adhere to the paper microstructure.
Contribution to the study of characterization on deposits formed in paper
Keywords: Calcium carbonate; Deposits; Detrimental substances; Starch; Wet end chemistry; Aggregates; Calcite; Calcium; Calcium alloys; Carbonate minerals; Carbonates; Carbonation; Gravimetric analysis; Microscopic examination; Microstructure; Organic compounds; Secondary emission; Thermogravimetric analysis; X ray analysis; X ray diffraction analysis; Optical microscopy